Improving Student Learning Outcomes through Discussion Methods and Increasing Student Learning Activities through Experimental Methods on Heat Transfer Material in Class X Physics at MAN 4 Pandeglang - Hanafi; Iwan Setiawan (PT FORMOSA CENDEKIA GLOBAL, 2022)
In class learning, the discussion method and the experimental method are needed so that students do not feel bored in carrying out learning activities. The success of the teaching and learning process can be seen from the achievement of KKM scores. In Class X Physics learning, only 64% of students achieved the KKM. Because of that, a class action research (PTK) was conducted, which included two cycles, and each cycle consisted of the stages of planning, implementing, observing, and reflecting. This research was conducted at class X MAN 4 Pandeglang Pandeglang in August - September 2022, with the aim of increasing student learning outcomes and student activity in the material Heat. Cycle I used discussion and experiment methods. In cycle II, classroom management techniques were added, organizing student study groups heterogeneously based on gender and student knowledge level. The results showed that the achievement of KKM for theory and practice increased, from 64% and 44.44% in pre-cycle, to 88% and 83.33% in cycle I, and 97% and 94.44 in cycle II. Research conclusions: The discussion method can improve student learning outcomes and the experimental method can increase student activity on heat material in class X